PHATIC COMMUNICATION: PSIKOLOGI KOMUNIKASI DALAM PEMBERITAAN ATTA-AUREL DI PORTAL KOMPAS - Ulfa Khairina (Jurnal Anifa: Studi Gender dan Anak, 2021)
Phatic communication is created from effective communication, especially from the pleasure characteristics that arise from communication feedback. Communication is done with a psychological approach in generally liked by netizens (communicants), those presented in online media. This study examines how psychological communication provides feedback from the communicator to the communicant, especially if the source of the news published is an entertainment figure. This study uses descriptive analysis techniques with data collection techniques for Kompas news documentation about Aurel's miscarriage in May 2021. From the results of the study it was found that the news broadcast by Kompas reaped pros and cons for netizens because of writing that used a communication psychology approach. the use of communication psychology raises phatic communication between communicants and communicators.